Answer:
A. Yes, but only within the domain x ≥ 0
Step-by-s+tep explanation:
What you need to know to solve the question:
1. To find an inverse function (f⁻¹(x)) of f(x), rearrange the equation in terms of f(x), in other words, it should be in the form of x = ...
2. Rules of rearranging equations
3. The domain of √x is: x ≥ 0, since you cannot find the square root of a negative number (i.e. < 0)
Find the inverse function of F(x):
According to principles 1 and 2:
F(x) = √x - 6
F(x) + 6 = √x
(F(x) + 6)² = x
x = (F(x) + 6)²
So, the inverse function is:
F⁻¹(x) = (x + 6)²
And since:
G(x) = (x + 6)²
G(x) = F⁻¹(x)
Therefore, the answer is, also in light of principle 3:
A. Yes, but only within the domain x ≥ 0